1999
DOI: 10.3177/jnsv.45.401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Meal Timing after Resistance Exercise on Hindlimb Muscle Mass and Fat Accumulation in Trained Rats.

Abstract: SummaryTo study the effect of meal timing after exercise on body composition, 20 male rats were assigned to either a group fed a meal right after exercise (R) or a group fed a meal 4h after exercise (L). Resistance exercise (squatting) was conducted from 6:00 to 7:00, 3d/wk for 10wk. Meals were consumed from 7:00 to 8:00 and from 19:00 to 20:00 for R, and from 11:00 to 12:00 and from 19:00 to 20:00 for L. The room was lighted from 7:00 to 19:00. After 10wk, the body weight was comparable between the groups. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…These previous studies (3,(4)(5)(6)(7)(8)(9)(10)(11)(12) proposed that the difference in timing of meal intake after exercise changed body composition and thereby resulted in altered bone acquisition. The purpose of the present study was to evaluate this hypothesis using the rats from a previous study (3) where the rats were fed a meal right after exercise or 4h after exercise during a 10-wk period of resistance exercise training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These previous studies (3,(4)(5)(6)(7)(8)(9)(10)(11)(12) proposed that the difference in timing of meal intake after exercise changed body composition and thereby resulted in altered bone acquisition. The purpose of the present study was to evaluate this hypothesis using the rats from a previous study (3) where the rats were fed a meal right after exercise or 4h after exercise during a 10-wk period of resistance exercise training.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the present study was to evaluate this hypothesis using the rats from a previous study (3) where the rats were fed a meal right after exercise or 4h after exercise during a 10-wk period of resistance exercise training. Thus, the data regarding bone measurement and bone mineral content and density were obtained and correlated to the difference in body composition of rats which were provided a meal at different times after exercising.…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies on the combined effects of ingestion of protein or amino acids and timing of exercise, with many researchers reporting that ingestion of protein or amino acids directly after exercise is effective in muscle protein synthesis (12)(13)(14)(15). In addition, some studies on ingestion of proteins or amino acids prior to exercise have shown the ingestion to be effective in muscle protein synthesis (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…The next study was conducted in rats to elucidate whether having a meal containing glycemic carbohydrates and protein soon after exercise promotes muscle protein accretion to a greater extent than ingesting a meal several hours later. 37 Twenty male Sprague-Dawley rats, which were meal-fed twice a day, were randomly assigned either to a group that received the post-exercise meal (rat chow diet) right after exercise (R group, n 5 10) or to a group receiving their meals 4 hours after exercise (L group, n 5 10). The rats underwent resistance exercise from hour 0600 to hour 0700, three times a week for 10 weeks using previously described resistance exercise (i.e., squatting) equipment designed for rats.…”
Section: Ingesting a Meal Soon After Exercise Over A Long Period Of Tmentioning
confidence: 99%